Study on the Pyrolysis Behaviors of Urea-Formaldehyde Resin and Rice Straw Mixed Pellets - Xiaoteng Li; Huilin Bing; Siyi Luo; Weiwei Zhang; Zongliang Zuo; Dongdong Ren (Frontiers in Energy Research, 2022)
In order to study the effect of biomass on the pyrolysis characteristics of urea-formaldehyde resin, the thermogravimetric experiments were carried out respectively using urea-formaldehyde resin (UF), rice straw (RS), and their mixed pellets with different proportions. The pyrolysis kinetics analysis was conducted. The results showed that the pyrolysis process of UF resin and mixed pellets could be divided into three stages: the drying and dehydration of the material, the rapid decomposition of volatile matter, and residue decomposition. The reaction order of UF resin and mixed pellets was discussed using the Coats–Redfern method, the activation energy of UF resin was 54.27 kJ/mol, and this value decreased with the addition of rice straw. As the mass ratio of UF resin to rice straw was 3:1, the activation energy achieved the lowest value, which means that the addition of rice straw was beneficial to the pyrolysis process of UF. In the process of pellet preparation, the falling strength and compressive strength of UF resin pellets can be improved by adding an appropriate proportion of rice straw. In this test, the yield of pyrolytic carbon reached the highest value of 23.93%, as the mass ratio of UF resin to rice straw was 3:2. When the mass ratio was 4:1, the highest liquid product yield of 43.21% was achieved.